Characterization of the Mechanical Strength, Resorption Properties, and Histologic Characteristics of a Fully Absorbable Material (Poly-4-hydroxybutyrate—PHASIX Mesh) in a Porcine Model of Hernia Repair. (28th May 2013) - Deeken, Corey R.; Matthews, Brent D.
Abstract : Purpose . Poly-4-hydroxybutyrate (P4HB) is a naturally derived, absorbable polymer. P4HB has been manufactured into PHASIX Mesh and P4HB Plug designs for soft tissue repair. The objective of this study was to evaluate mechanical strength, resorption properties, and histologic characteristics in a porcine model. Methods . Bilateral defects were created in the abdominal wall of n = 20 Yucatan minipigs and repaired in a bridged fashion with PHASIX Mesh or P4HB Plug fixated with SorbaFix or permanent suture, respectively. Mechanical strength, resorption properties, and histologic characteristics were evaluated at 6, 12, 26, and 52 weeks (n = 5 each). Results . PHASIX Mesh and P4HB Plug repairs exhibited similar burst strength, stiffness, and molecular weight at all time points, with no significant differences detected between the two devices (P > 0.05 ). PHASIX Mesh and P4HB Plug repairs also demonstrated significantly greater burst strength and stiffness than native abdominal wall at all time points (P < 0.05 ), and material resorption increased significantly over time (P < 0.001 ). Inflammatory infiltrates were mononuclear, and both devices exhibited mild to moderate granulation tissue/vascularization. Conclusions . PHASIX Mesh and P4HB Plug demonstrated significant mechanical strength compared to native abdominal wall, despite significant material resorption over time. Histological assessment revealed a comparable mild inflammatory response and mild to moderate granulation tissue/vascularization.